2010
DOI: 10.2105/ajph.2008.154153
|View full text |Cite
|
Sign up to set email alerts
|

A Worksite Obesity Intervention: Results From a Group-Randomized Trial

Abstract: The participatory process appeared to be an effective means for stimulating change. The intervention may have slowed and perhaps reversed the tendency of adults to gain weight progressively with age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
92
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(92 citation statements)
references
References 10 publications
0
92
0
Order By: Relevance
“…For example, a construction worker must lift heavy objects, while a white-collared employee may spend majority of his or her working hours at a desk. Considering the amount of time and money obesity in the workplace has cost, companies have targeted their focus on developing interventions that are tailored to different occupational settings [33,35,37,39,40]. In turn, employees often know what makes a workplace vibrant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a construction worker must lift heavy objects, while a white-collared employee may spend majority of his or her working hours at a desk. Considering the amount of time and money obesity in the workplace has cost, companies have targeted their focus on developing interventions that are tailored to different occupational settings [33,35,37,39,40]. In turn, employees often know what makes a workplace vibrant.…”
Section: Discussionmentioning
confidence: 99%
“…Implementation of obesity prevention or weight management intervention programs and strategies in the workplace, in a form of health promotion or worker wellness programs aimed at weight, nutrition, stress, and physical activity, taking into consideration the obesity rates of today, may be important for employers to consider [33][34][35][36][37][38][39][40] ( Table 2 [42]. In a recent literature review of the effectiveness of workplace health interventions by Schröer et al, beneficial health effects have been found in interventions aimed at workplace nutrition and multi-component physical activity, both of which, when combined, showed a greater effect on weight loss over solely one or the other; however, this review have not found any evidence of increased efficacy associated with any specific intervention reviewed [43].…”
Section: Obesity and Interventionsmentioning
confidence: 99%
“…Our response rates for clients and programs were acceptable (78 to over 90 %), but low to moderate (50 %) for agencies relative to the field. Many studies of quality improvement in specific sites or applying CBPR to health rely on convenience samples, 7,38,[55][56][57][58][59][60][61] and use integrated systems or households or settings in government districts. 39,49,[62][63][64][65][66] The study findings are based on client self-report and may not accurately reflect actual service use due to problems such as client recall.…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies typically lack detailed rationale for sampling procedures or rely on convenience samples of sites with individual randomization. Sites, when matched, are selected by convenience, or within integrated health care systems or government districts (Blumenthal, Smith, Majett, & Alema-Mensah, 2010;Corbie-Smith et al, 2003;Cordasco et al, 2009;Perry, Stigler, Arora, & Reddy, 2008;Siegel, Prelip, Erausquin, & Kim, 2010;Wilson et al, 2008). Few published manuscripts provide guidance on how to maintain the scientific goals of feasibility, validity (internal and external), and methodological integrity alongside partnership principles of transparency, equity, and trust.…”
Section: Building Coalitions and Partnerships For Health Promotionmentioning
confidence: 99%